Blasting neuroblastoma using optimal control of chemotherapy - Craig Collins; K. Renee Fister; Bethany Key; Mary Williams (Mathematical Biosciences and Engineering)
A mathematical model is used to investigate the effectiveness of thechemotherapy drug Topotecan against neuroblastoma. Optimal control theoryis applied to minimize the tumor volume and the amount of drug utilized.The model incorporates a state constraint that requires the level ofcirculating neutrophils (white blood cells that form an integral part of the immune system) to remain above an acceptable value. The treatmentschedule is designed to simultaneously satisfy this constraint and achievethe best results in fighting the tumor. Existence and uniqueness of the solution of theoptimality system, which is the state system coupled with the adjoint system, is established. Numericalsimulations are given to demonstrate the behavior of the tumor and the immune systemcomponents represented in the model.